On the study of industrial waste sites on the Karelian Isthmus/Russia using the RMT and CSRMT methods - Saraev, Alexander; Simakov, Alexander; Tezkan, Buelent; Tokarev, Igor; Shlykov, Arseny (ELSEVIER, 2020)
Radiomagnetotelluric (RMT) and Controlled Source Radiomagnetotelluric (CSRMT) measurements were carried out on landfills of industrial wastes located on the Karelian Isthmus/Russia. The RMT and CSRMT data were interpreted using the 2D inversion techniques, and the 2D conductivity structures of the investigated industrial waste sites were derived. The RMT method is based on measurements of electromagnetic fields of remote radio transmitters in a frequency range of 10-1000 kHz or in a frequency range of 1-1000 kHz by using a controlled source (CSRMT method). A landfill in the settlement Morozova near St. Petersburg was formed as a result of a long-term warehousing of toxic wastes by the sulfuric acid manufacture. Soils and ground waters were polluted with salts of heavy metals. In the adjacent to the landfill territory, investigations were realized by the RMT method and a polluted zone was determined. This zone is traced up to the coast of the Ladoga Lake and the Neva River. It constitutes a potential danger because the Neva River is used for the water supply of St. Petersburg. Another landfill of debris in a former sandy career is located in the Vyborg area. The high conductivity and a relative large thickness of the wastes did not allow us to map the bottom of the landfill by the RMT method using the frequency range of 10-1000 kHz. Therefore, CSRMT measurements with an extended frequency range up to 1 kHz were carried out on this landfill, and the 2D inversion of the CSRMT data clearly showed the lateral and vertical extension of it. (C) 2020 Elsevier B.V. All rights reserved.